Bidirectional relationships among complex PTSD, dissociation, and psychotic symptoms in two samples - Hong Wang Fung; Anson Kai Chun Chau; Stanley Kam Ki Lam; Grace Wing Ka Ho; Colin A. Ross; Ming Yu Claudia Wong; Edward K. S. Wang; Wai Tong Chien; Janet Yuen-Ha Wong (European Journal of Psychotraumatology)
Background: Although trauma-related symptoms (e.g. complex PTSD and dissociative symptoms) and psychotic symptoms often co-occur, little is known about the complex relationships among these symptoms over time.Objective: This study examined the bidirectional relationships among complex PTSD symptoms, dissociative symptoms, and positive symptoms of psychosis.Methods: This study analyzed available longitudinal data from two convenience samples (Sample 1: N = 214, Chinese-speaking adults; Sample 2: N = 301, English-speaking adults). Participants in both samples completed validated measures of ICD-11 complex PTSD (that included measurement of ‘classical’ PTSD), dissociation, and positive symptoms of psychosis at baseline and follow-up, six months (Sample 1) or 12 months (Sample 2) apart. A cross-lagged panel model was used to examine the longitudinal relationship between trauma-related symptoms and psychotic symptoms in each sample.Results: In Sample 1, baseline dissociative symptoms significantly predicted positive symptoms of psychosis at follow-up. In Sample 2, no significant longitudinal relationships between trauma-related and psychotic symptoms were observed. In both samples, baseline disturbances in self-organization (DSO) symptoms predicted ‘classical’ PTSD symptoms at follow-up.Conclusion: This study made the first attempt to examine the longitudinal relationships among ICD-11 complex PTSD symptoms, dissociative symptoms, and psychotic symptoms. The inconsistent findings point to the importance of further research on the longitudinal relationships between trauma-related and psychotic symptoms. Moreover, our results indicate that addressing DSO symptoms may be important in the prevention and treatment of PTSD symptoms.